Legislative regulation of assisted reproductive technologies as a direction for the development of medical tourism in Ukraine - Astafiev , Denys (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The relevance of the study is due to the legal uncertainty of the scope of application of assisted reproductive technologies as a form of realization of the right to health care and maternity. It is revealed that reproductive medicine, according to the existing segments of the world market, is a type of medical tourism which in Ukraine requires careful analysis and proper legislative regulation. The purpose of the article is to determine the role of medical tourism in the provision of services in the field of assisted reproductive technologies, as well as the problematic aspects of legislative regulation of assisted reproductive technologies as a direction of medical tourism development in Ukraine. The author examines the reasons for the rapid development of medical tourism in the world, as well as the factors that will contribute to the development of this sphere in Ukraine. The author concludes that surrogacy, import and export of donor human reproductive cells should be properly regulated by law in the coming years. Ukraine has already become a center of medical tourism, but unregulated conditions potentially increase cases of fraud, smuggling, and violations of human rights and freedoms, including those of children, parents, and surrogate mothers. The legal regulation of such a sphere of social relations as reproductive medicine is an extremely important, multifaceted and controversial issue that affects both public and private interests. Of course, the use of reproductive technologies, including gamete and embryo donation and surrogacy, has many controversial ethical, political, economic and, of course, legal aspects. Whether and how to allow surrogacy, whether to allow only altruistic surrogacy and prohibit commercial surrogacy. A controversial issue is whether to allow or prohibit the export of gametes and embryos in the context of the demographic crisis in Ukraine. Legislative regulation of the procedure for importing/exporting gametes and embryos seems interesting for further research.